2018
DOI: 10.3389/fpls.2018.01056
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage and Chromatin Conformation Changes Confer Nonhost Resistance: A Hypothesis Based on Effects of Anti-cancer Agents on Plant Defense Responses

Abstract: Over the last decades, medical research has utilized DNA altering procedures in cancer treatments with the objective of killing cells or suppressing cell proliferation. Simultaneous research related to enhancing disease resistance in plants reported that alterations in DNA can enhance defense responses. These two opposite perspectives have in common their effects on the center for gene transcription, the nuclear chromatin. A review of selected research from both anticancer- and plant defense-related research p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 126 publications
(181 reference statements)
0
13
0
Order By: Relevance
“…Poly-L-lysine molecules and many other cationic molecules are efficient elicitors of defense responses in pea endocarp tissue, some of which are compounds that can reside in the DNA minor groove [ 6 ]. This proposed action directly on plant chromatin helps confirm that a mechanism by-passing recognition at the plant membrane may initiate a major route towards defense gene regulation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poly-L-lysine molecules and many other cationic molecules are efficient elicitors of defense responses in pea endocarp tissue, some of which are compounds that can reside in the DNA minor groove [ 6 ]. This proposed action directly on plant chromatin helps confirm that a mechanism by-passing recognition at the plant membrane may initiate a major route towards defense gene regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Smaller compounds called phytoalexins (e.g., pisatin) ( Figure 2) [33] are newly synthesized in plants following pathogen challenge. The pisatin pathway is activated by an array of DNA-specific agents [6,8] and by many non-pathogenic organisms. Virulent organisms contacting plant tissue trigger some of the same responses as the avirulent pathogens [3].…”
Section: At-rich Dna Sequences In Pre-promoter Region Of Pea Hmg a Genementioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that sDNA can trigger ROS- and MAPK-dependent signaling cascades [20], alter the CpG DNA methylation status (hypomethylation), and elicit defense-related responses [21]. Moreover, DNA damage and alteration of the primary chromatin structure were shown to induce the expression of defense-related genes [22, 23]. Elucidation of the plant-specific receptors that recognize extracellular sDNA as DAMPs could advance our knowledge on sDNA-dependent danger signaling in plant cells.…”
Section: Introductionmentioning
confidence: 99%